Endothelial Injury in Diving: Atomic Force-, Electronic-, and Light-Microscopy Study of the Ovine Decompressed Blood Vessels - Arieli, Ran (Frontiers in Physiology, 2021)
We suggested that nanobubbles which appear at the active hydrophobic spots (AHS) at luminal aspect of blood vessels, are the gas micronuclei from which decompression bubbles evolve, and the endothelial injury during decompression is due to the tearing off cell membranes with the detaching bubbles. Ovine blood vessels were stretched over polycarbonate plates or glass microscopic slides and were exposed under saline to hyperbaric pressure (1013 kPa, 19 h). Following decompression the blood vessels were photographed for identification (by bubble formation) of the AHS. Nanobubbles could not be demonstrated at the AHS, using atomic force microscopy (AFM) because of the roughness of the surface which disabled close contact of the probe. In the electron microscopy, no endothelial cells were observed in samples from the area near the AHS, but the underlying elastin layer of the intima adjacent to the media. Some intact endothelial cells were observed only in locations far from an AHS. In the optical microscopy, no endothelial cells were observed in blood vessels in close proximity to the AHS and in some sections, debris or a detached cluster of endothelial cells were observed. Intact endothelial cells could be found at sites distant from an AHS. The present study supports our assumption, where detached bubbles tear off endothelial cells and cause the initial endothelial injury following decompression.